2014
DOI: 10.1155/2014/857462
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations of Noise Control in Planetary Gear Set by Phasing

Abstract: Now a days reduction of gear noise and resulting vibrations has received much attention of the researchers. The internal excitation caused by the variation in tooth mesh stiffness is a key factor in causing vibration. Therefore to reduce gear noise and vibrations several techniques have been proposed in recent years. In this research the experimental work is carried out to study the effect of planet phasing on noise and subsequent resulting vibrations of Nylon-6 planetary gear drive. For this purpose experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Experimental investigation and validation of the benefits of planet phasing were carried out by Gawande and Shaikh. 11 The results show that the dynamic planetary gear response can be minimized using such phasing.…”
Section: Introductionmentioning
confidence: 96%
“…Experimental investigation and validation of the benefits of planet phasing were carried out by Gawande and Shaikh. 11 The results show that the dynamic planetary gear response can be minimized using such phasing.…”
Section: Introductionmentioning
confidence: 96%
“…They varied several factors including the contact ratio of tooth profile and approach of finishing the gears, for them to be able to evaluate the measured data. Gawande and Shaikh [16] conducted an experimental investigation of noise reduction in planetary gear set by application of phasing. When results obtained by application of phasing system and without application of phasing system at 1200 rpm are compared, it is revealed that when meshing phase is applied, the level of noise recorded in the planetary gear set was significantly lower than the one in the planetary gear set without a meshing phase.…”
Section: Introductionmentioning
confidence: 99%
“…Although the nature of parametric vibration is a well-known and investigated phenomenon [24][25][26], this problem is remaining a challenge. Some methods are proposed of gears profile modification [27] and gears phasing [9,28] with taking into account contact friction and transmission errors [29]. Those methods are applicable only at the design stage.…”
Section: Introductionmentioning
confidence: 99%